ANALISIS KUALITAS PENGGUNAAN OSPOL PADA SISTEM LOGISTIK PEMESANAN FARMASI DENGAN METODE GAP ANALYSIS - Abdiarta Aswinabawa (Jurnal Strategi Pemasaran, 2022)
The purpose of this study was to measure the gap in the quality of using OSPOL website-based applications based on customer expectations and to find out improvements that could be made to improve the performance of OSPOL website-based applications. This type of research is quantitative research, the research variable is the website quality dimension. The technique of collecting data is using a questionnaire, the number of samples is 91 samples. The data analysis technique used gap analysis. The findings of this study indicate that there is a negative gap between the perceived performance of customers from the OSPOL website and the level of interest of the respondents. There is a negative gap between the standards set by PT MAS and the level of customer expectations based on the level of importance of each feature or indicator from the OSPOL website. There is a negative gap between the standards set by PT MAS and the actual performance perceived by customers from the OSPOL website.